Perspectives on Poverty in India : Stylized Facts from Survey Data - World Bank (World Bank, 2012)
This report's objective is to develop the evidence base for policy making in relation to poverty reduction. It produces a diagnosis of the broad nature of the poverty problem and its trends in India, focusing on both consumption poverty and human development outcomes. It also includes attention in greater depth to three pathways important to inclusive growth and poverty reduction harnessing the potential of urban growth to stimulate rural-based poverty reduction, rural diversification away from agriculture, and tackling social exclusion. This report shows that urban growth, which has increasingly outpaced growth in rural areas, has helped to reduce poverty for urban residents directly. In addition, evidence appears of a much stronger link from urban economic growth to rural poverty reduction. Stronger links with rural poverty are due to a more integrated economy. Urban areas are a demand hub for rural producers, as well as a source of employment for the rural labor force. They are aiding the transformation of the rural economy out of agriculture. In urban areas, it is small and medium-size towns, rather than large cities, that appear to demonstrate the strongest urban-rural growth links. Urban growth also stimulates rural-urban migration. But although some increase in such migration has occurred over time, migration levels in India remain relatively low compared to other countries.